POLITIK KETAHANAN PANGAN PAKISTAN POST – BLACK SEA GRAIN INITIATIVE - Suba, Almadhea; Nugraha, Imam Fadhil (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
: HAM is basically God's greatest gift to man in carrying out his duties and functions as khalifatullah without discrimination between one another. However, there are some people who think that in Islamic law does not find the formulation of human rights as the concept of Western-style human rights but only contains the rules of duty and duty to obey God and His law alone. Based on the searches of the verses of the Qur'an and Sunnah it is concluded that Islamic law has formulated the regulation and protection of human rights for human beings. Unlike anthrophocentric Western human rights, human rights in Islamic law not only recognize the right of human beings (huququl 'ibad) but it is based on the basic human obligation to serve Allah Almighty (huququllah). Islamic law establishes the main principles in the protection of human rights that are significant with the objectives of Islamic law namely the principle of protection of religion (hifdz al-din), soul (hifdz al-nafs), reason (hifdz al-'aql), descendants (hifdz al-nasl) and treasure (hifdz al-mal).